E-Learning readiness and its correlates among secondary school teachers in Nablus, Palestine - Trayek, Fuad; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (2013)
This study explored the readiness levels of the secondary school teachers in Nablus to adopt e-learning in four important aspects: technological, psychological, equipment, and overall e-learning readiness, and the influence of gender on these aspects. A total of 475 teachers (236 males and 239 females) from 24 secondary schools in Nablus participated in the survey that employed a 23-item questionnaire measuring the readiness constructs on a 5-point Likert scale. The items were first content validated by experts and pilot-tested before being administered to the respondents. The data were analyzed using descriptive statistics, independent-samples t-tests, Cohen’s d for effect sizes, and Pearson’s product-moment correlation tests. The results showed that Nablus teachers were quite psychologically ready to use e-learning, but this aspect was not equally supported by technological and equipment readiness. Technological, equipment and psychological readiness were all found to be significant correlates of e-learning readiness with quite strong influences. Statistically significant gender differences were detected for technological, equipment and overall e-learning readiness, but not for psychological readiness. However, the magnitude of the differences was considered small based on the interpretation of Cohen’s d for effect sizes. The findings have important implications on what the Palestinian Ministry of Education and Nablus school principals need to put in place in order to better prepare their teachers and schools for e-learning.